Analysis of The Use of Rumpang Techniques in Description Writing Skills Assisted by Image Media - Quddus, Ilham Mauliddul; Hermansyah, Hermansyah; Murjainah, Murjainah (PrimaryEdu : Journal of Primary Education, 2023)
The purpose of this study was to determine the use of the gap technique in the writing skill descriptions with the help of image media. The research method which was used in this research was descriptive qualitative method with the data collection techniques by using the observations, interviews, and documentations. The results of this study will contain the data extract that will describe the data presentation. This study used the observation, interview and documentation techniques to collect the data. The results of the study on the use of the gap techniques from the data obtained in the 5th grade was the teacher must prepare in the learning process by using the gap technique are as follows, the teacher prepares a paragraph story, the teacher prepares a paragraph that has been crossed for the students to fill in.